Beregszászi magyar tannyelvű iskolába járó ötödikesek identitástudata és a nyelvtanulás közötti összefüggések - Huszti Ilona; Густі Ілона (Poliprint Kft., 2009)
Egy folyamatban lévő vizsgálat részeredményeit szeretném bemutatni rávilágítva arra, hogyan befolyásolja a beregszászi magyar iskolákban tanuló gyerekek identitását az a tudat, sőt, időnként kényszer, hogy kötelező megtanulni és tudni az államnyelvet (az ukránt). A hatályos törvények értelmében ugyanis Ukrajnában csak azok jelentkezhetnek felsőoktatási intézménybe, akik emelt szintű érettségi vizsgát tettek ukrán nyelvből, és legalább elégséges eredményt értek el.

Abstract. The article describes the results of a questionnaire survey about the relationships among identity, mother tongue and language use of 92 ten to twelve year old Hungarian learners in Beregszász/Berehovo, Ukraine. The study aimed to investigate how mother tongue, language use by the learners, and their identity are related. In many of the families Ukrainian is also used besides Hungarian. The results refuted the hypothesis that learners’ mother tongue and national identity coincide. The correlational analysis did not show significant relationship between the first language and identity. However, the findings indicate correlation between identity and home language (r=.4), meaning that the language used at home is a stronger indicator of identity of learners of Beregszász/Berehovo Hungarian schools.
Relationships between the identity and language learning of Beregszász/Berehovo Hungarian fifth graders
https://opac3.brff.monguz.hu:443/hu/record/-/record/92479
Keywords: Beregszász; magyar tannyelvű iskola; ötödikesek; identitástudat; nyelvtanulás